Implementación de la NIC 41 AGRICULTURA en el Registro Contable de las Empresas Agrícolas Colombianas: Implicaciones y Beneficios (2020)
In light of the lack of accuracy in the accountable methods regarding the Decree 2649 of 1993 and the demands of an international and globalized market, it´s neccesary to modernize and standarize the accountable methods of the colombian agricultural companies. This modernization and adequacy to the international standards act as an increase in productivity, competitiveness and profitability to those companies that adopt it. The different accountable researches made in Colombia as well as in other places all over Latin America in relation to the adoption of the standard NIC 41 determine that its implementation is a big step forward for the agricultural companies. Due to the proven implications in several agricultural crops in different territories, the entrepreneurs and accountants need greater training in this field in order to achieve a majority adoption of this standard. This would lead to an increase in competitiveness and would strengthen the colombian business network facing the new challenges of the global market.